Host-Specific Phenotypic Plasticity of the Turtle Barnacle Chelonibia testudinaria: A Widespread Generalist Rather than a Specialist - Cheang, C. C.; Tsang, L. M.; Chu, K. H.; Cheng, I.-J.; Chan, B. K. K. (PLoS ONE, 2013)
Turtle barnacles are common epibionts on marine organisms. Chelonibia testudinaria is specific on marine turtles whereas C. patula is a host generalist, but rarely found on turtles. It has been questioned why C. patula, being abundant on a variety of live substrata, is almost absent from turtles. We evaluated the genetic (mitochondrial COI, 16S and 12S rRNA, and amplified fragment length polymorphism (AFLP)) and morphological differentiation of C. testudinaia and C. patula from different hosts, to determine the mode of adaptation exhibited by Chelonibia species on different hosts. The two taxa demonstrate clear differences in shell morphology and length of 4–6th cirri, but very similar in arthropodal characters. Moreover, we detected no genetic differentiation in mitochondrial DNA and AFLP analyses. Outlier detection infers insignificant selection across loci investigated. Based on combined morphological and molecular evidence, we proposed that C. testudinaria and C. patula are conspecific, and the two morphs with contrasting shell morphologies and cirral length found on different host are predominantly shaped by developmental plasticity in response to environmental setting on different hosts. Chelonibia testudinaria is, thus, a successful general epibiotic fouler and the phenotypic responses postulated can increase the fitness of the animals when they attach on hosts with contrasting life-styles.